Serum Prealbumin and Echocardiography Parameters Predict Mortality in Peritoneal Dialysis Patients - Min Ye; Jianbo Li; Yanqiu Liu; Wei He; Hong Lin; Rui Fan; Cuiling Li; Wei Li; Jingwei Zhang; Huiling Huang; Fengjuan Yao (Karger Publishers, 2020)
Aim: Protein-energy malnutrition and cardiovascular (CV) disease predisposes patients with end-stage renal disease (ESRD) on dialysis to a high risk of early death, but the prognostic value of prealbumin (PAB) and echocardiographic indices in ESRD patients treated with maintenance peritoneal dialysis (PD) remains unclear. Methods: A total of 211 PD patients (mean age 49.2 ± 15.4 years, 51.7% male) were prospectively studied. PAB and echocardiography parameters were recorded at baseline. Follow-up (mean ± SD: 33.7 ± 17.3 months) was conducted based on hospital records, clinic visits, and telephone reviews, to record death events and their causes. Results: In the Cox proportional hazards model, PAB and the echocardiographic parameters listed below were found to be optimal predictors of all-cause mortality: PAB (p = 0.003), aortic root diameter (ARD) (p = 0.004), interventricular septum end-diastolic thickness (IVSd) (p = 0.046), and left ventricular end-diastolic diameter index (LVEDDI) (p = 0.029). Of the above-mentioned factors, PAB (p = 0.018), ARD (p = 0.031), and IVSd (p = 0.037) were independent predictors of CV mortality in PD patients. Of note, malnutrition, degradation of the aorta, and myocardial hypertrophy are also known death risk factors in the general population. The all-cause mortality and CV death rate significantly increased as the number of risk factors increased, reaching values as high as 40 and 22% in patients who had all of the risk factors, i.e., abnormal PAB, ARD, and IVSd (p < 0.001 and p = 0.011). Conclusion: In PD patients, low serum PAB and abnormal echocardiographic parameters together were significantly associated with all-cause mortality and CV death, independently of other risk factors. These risk factors for death in PD are similar to those in the general population. Noticeably, the combination of echocardiographic parameters and PAB could provide additional predictive value for mortality in PD patients. In light of these findings, more studies in an optimal model containing PAB and echocardiographic parameters for the prediction of outcomes in ESRD are required.